Noise and the efferent auditory system activation: A scoping review - Rahmat, Sarah; Dzulkarnain, Ahmad Aidil Arafat; Amirullah, Nur Afiqah; Mohd Saufi, Mohd Amir Faisal; ,; , (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia, 2019)
Introduction: The efferent auditory system is a descending system that connects the central and peripheral auditory system. One way to activate the system is by stimulating the contralateral ear while measuring the response from the ipsilateral ear. The objective of this paper is to conduct a scoping review that 1) catalogues the different types of contralateral acoustic stimuli used to activate the efferent auditory system, and 2) identifies the methods used to measure the activation of the efferent auditory system.